Can stem cells be used to generate new lungs? Ex vivo lung bioengineering with decellularized whole lung scaffolds. Issue 6 (25th July 2013) - Wagner, Darcy E.; Bonvillain, Ryan W.; Jensen, Todd; Girard, Eric D.; Bunnell, Bruce A.; Finck, Christine M.; Hoffman, Andrew M.; Weiss, Daniel J.
Abstract For patients with end‐stage lung diseases, lung transplantation is the only available therapeutic option. However, the number of suitable donor lungs is insufficient and lung transplants are complicated by significant graft failure and complications of immunosuppressive regimens. An alternative to classic organ replacement is desperately needed. Engineering of bioartificial organs using either natural or synthetic scaffolds is an exciting new potential option for generation of functional pulmonary tissue for human clinical application. Natural organ scaffolds can be generated by decellularization of native tissues; these acellular scaffolds retain the native organ ultrastructure and can be seeded with autologous cells towards the goal of regenerating functional tissues. Several decellularization strategies have been employed for lungs; however, there is no consensus on the optimal approach. A variety of cell types have been investigated as potential candidates for effective recellularization of acellular lung scaffolds. Candidate cells that might be best utilized are those which can be easily and reproducibly isolated, expanded in vitro, seeded onto decellularized matrices, induced to differentiate into pulmonary lineage cells, and which survive to functional maturity. Whole lung cell suspensions, endogenous progenitor cells, embryonic and adult stem cells and induced pluripotent stem (iPS) cells have been investigated for their applicability to repopulate acellular lung matrices. Ideally, patient‐derived autologous cells would be used for lung recellularization as they have the potential to reduce the need for post‐transplant immunosuppression. Several studies have performed transplantation of rudimentary bioengineered lung scaffolds in animal models with limited, short‐term functionality but much further study is needed.